The parallel programming of landing position in saccadic eye movement sequences - McSorley, Eugene; Gilchrist, Iain D.; McCloy, Rachel (Journal of Vision, 2020)
Saccadic eye movements occur in sequences, gathering new information about the visual environment to support successful task completion. Here, we examine the control of these saccadic sequences and specifically the extent to which the spatial aspects of the saccadic responses are programmed in parallel. We asked participants to saccade to a series of visual targets and, while they shifted their gaze around the display, we displaced select targets. We found that saccade landing position was deviated toward the previous location of the target suggesting that partial parallel programming of target location information was occurring. The saccade landing position was also affected by the new target location, which demonstrates that the saccade landing position was also partially updated following the shift. This pattern was present even for targets that were the subject of the next fixation. Having a greater preview about the sequence path influenced saccade accuracy with saccades being less affected by relocations when there is less preview information. The results demonstrate that landing positions from a saccade sequence are programmed in parallel and combined with more immediate visual signals.